Linguistic Change and Generative Theory Essays from the UCLA Conference on Historical Linguistics in the Perspective of Transformational Theory, February 1969 - Stockwell, Robert S. (Indiana University Press, 1972)
Linguistic Change and Generative Theory presents nine papers by leading scholars in the field of transformational linguistic theory. Dealing mostly with phonological change, the papers demonstrate that transformational theory has unique insights to contribute to historical linguistics. Contributors are Emmon Bach, Robert Harms, Charles-James Bailey, T. G. Bever, D. T. Langendoen, James Foley, William Labov, Robin Lakoff, Sanford Schane, Theo Vennemann, and Arnold Zwicky. Includes 16 line drawings, special charts and equations.